The effects of incorporating individual factors within target engagement and decision making shooting performance of elite shooters - Scribner, D.; Talarico, M.; Morelli, F. (DEVCOM Analysis Center, 2023)
This study was designed to use quantitative metrics to identify whether or not a theoretical general model of Individual Factors (IFs) on marksmanship performance could be supported (Scribner & Morelli, 2020). The proposed model outlines and connects factors that may influence shooting and marksmanship performance including weapon, ammunition, and target characteristics as well as IF of the shooter (Scribner & Morelli, 2020). This study is the first phase of a larger, multi-study effort to better understand the impact of IFs on shooting performance across varying levels of marksmanship expertise.